THE BALANCE OF LEARNING MODEL DEVELOPMENT AT ELEMENTARY SCHOOL AGE - Widiastuti Widiastuti; Tomy Ariyanto (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
This research aims to produce a balance learning model for elementary school age. This study used Research & Development (R&D) method. Instrument used in this research is balance a Modified Test of Dynamic Balance applied to collect data in children of elementary school age. Those step are: (1) need analysis, (2) expert justment; (3) limited trial (small group trial); and (4) main trial (field testing). Effectiveness of implementation of balance learning model in children of elementary school age using sample of 70 students by "t-testâ€ techniqe. Pre test and post test were obtained the average result of pre test of 39,85 and average post test 68,42. The total of pre test and post test was 28,57 with deviation standard of 8,89 and t value pf 26,88 so the data is declared significant. It means balance model in children at elementary school age is effective to improve elementary school balance. Based on results of research it is concluded that the balance model in children at elementary school age being developed has a significant effectiveness.